A NOVEL REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD FOR SIMULTANEOUS ESTIMATION OF ELLAGIC ACID, QUERCETIN, AND PIPERINE IN AYURVEDIC FORMULATIONS - Shaikh, Sultana; Jain, Vandana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to develop a novel, accurate, precise, and linear reverse-phase high-performance liquid chromatographic (RP-HPLC) method for simultaneous qualitative and quantitative estimation of ellagic acid, quercetin, and piperine in different Ayurvedic formulations and validate as per the International Conference on Harmonization guidelines. Methods: In the present work, a good chromatographic separation was achieved isocratically using a shim-pack HPLC C18 column (4.6×250 mm, 5 μm) and a mobile phase consisting of 0.02 M potassium dihydrogen orthophosphate buffer (pH adjusted to 3.5 with orthophosphoric acid) and acetonitrile in the ratio 60:40, a flow rate of 1.2 ml/min and column temperature maintained at 35°C. The effluents obtained were monitored at 255 nm with ultraviolet-visible detector. Results: The retention time of ellagic acid, quercetin, and piperine was found to be 1.65 min, 2.94 min, and 14.57 min, respectively. The linearity of ellagic acid, quercetin, and piperine was tested in the range of 6–14 ppm, 3–11 ppm, and 3–13 ppm, respectively. The correlation coefficient for ellagic acid, quercetin, and piperine was found to be 0.997, 0.993, and 0.99, respectively. The high recovery values (98–102%) indicate a satisfactory accuracy. The low percent relative standard deviation values in the precision study reveal that the method is precise. Conclusion: The developed method is novel, simple, precise, rapid, accurate, and reproducible for simultaneous quantitative estimation of ellagic acid, quercetin, and piperine in Ayurvedic formulations. Hence, the developed method can be used for quantitative analysis and quality control of extracts and commercial samples of other plant species and formulations containing these three markers.